Gentrification on the Move. New Dynamics in Spanish Mature Urban-Tourist Neighborhoods - Josefina Domínguez-Mujica; Jesús M. González-Pérez; Juan Manuel Parreño-Castellano; Dolores Sánchez-Aguilera (Urban Science, 2021)
Mature tourism neighborhoods are a valuable laboratory for the study of socio-urban processes. In them, it is possible to analyze the urban transformations and social changes linked to tourism cycles: those corresponding to the stage of tourism involvement, development, and consolidation; those of stagnation and urban decline; and those of tourism rejuvenation and urban rehabilitation. Currently, there are indications of a fourth cycle, where vacation rentals and the arrival of new groups of foreigners are causing a tourism gentrification process. In this context, the aim of this work is to study the socio-urban transformations of two mature tourism neighborhoods in Palma (El Terreno) and Las Palmas de Gran Canaria (Santa Catalina-Canteras) and detect this tourism gentrification process. The analysis is based on indicators of resident population (total population and foreigners by nationalities), housing (holiday rental market and real estate market), and socio-economic levels (income), which allows us to detect the existence of a new urban-tourism cycle. This, supported by strong investments associated with rehabilitation plans, is producing the substitution of foreigners from the South for those from the North, changing from residential rental to vacation rentals, in a context of elitization.